Uncovering the rate of the martensitic transformation in superheated shape memory alloy wires. (15th January 2023) - Dana, Asaf; Bronstein, Emil; Faran, Eilon; Honkimäki, Veijo; Liss, Klaus-Dieter; Shilo, Doron
Graphical abstract: Abstract: The martensitic transformation in shape memory alloys is known to be very fast. However, its rate in bulk materials that serve in common actuator applications is still an open question. In this study, the martensitic transformation is induced by a high-voltage microsecond superheating pulse in a polycrystalline NiTi shape memory alloy wire and its rate is tracked using time resolved X-ray diffraction by synchrotron radiation. The study employs a novel experimental technique that allows for multi-frame time-resolved detection with a temporal resolution below 1 µs, demonstrating an order-of-magnitude improvement compared to previous time-resolved synchrotron studies. Results show that the transformation begins at the moment the wire temperature reaches the transformation temperature and the transformation rate follows the rate of heating, completing most of the process within approximately 1 µs. Yet, part of the transformation continues at much slower time scales of several tens of microseconds.